Factors Associated with the Incidence of Low Birth Weight (LBW) Babies at RSIA Masyita in Makassar City - St Subriani; Samsir syam (Viva Medika, 2023)
Based on data obtained from RSIA Masyita, in 2020 there were 33 mothers who gave birth. The aim of this research is to determine the factors associated with the incidence of Low Birth Weight Infants at RSIA Masyita Makassar 2022. This research uses analytical methods using a Cross Sectional Study approach to determine the factors associated with the incidence of Low Birth Weight Infants at RSIA Masyita Makassar with a total population of 412 people and a total sample of 203 people using the Simple Random Sampling technique. The results of statistical tests using Chi-Square were obtained for the variable maternal age, the value P = 0.000 < α = 0.050, meaning that there is a relationship between maternal age and the incidence of LBW. For the parity variable, the value of P = 0.001 <α = 0.050 means that there is a relationship between parity and the incidence of LBW. For the variable spacing of maternal pregnancies, the value of P = 0.000 < α = 0.050 means that there is a relationship between the spacing of pregnancies and the incidence of LBW. For the variable twin pregnancy, the value of P = 0.000 < α = 0.050 means that there is no relationship between twin pregnancy and the incidence of LBW. The conclusion of the four variables namely maternal age, parity, pregnancy spacing, and multiple pregnancies are related to the incidence of LBW at RSIA Masyita Makassar. Keywords: Age, Parity, Distance of Pregnancy, Gemeli